Tata laksana pemotongan kuku pada sapi perah - . Hinarno; Henny Endah Anggraeni; Fathul Bari; Asep Suwandi; Iyus Setiawan; . Rukmana (School of Veterinary Medicine and Biomedical Sciences, Bogor Agricultural University, 2018)
Hoof trimming aims to restore normal hoof position, cleaning up dirts at slit hoof, avoiding lameness, facilitate early detection of laminitis and infection. This final report is purpose to explain the hoof treatment and trimming in dairy cows at Koperasi Peternakan Sapi Bandung Utara (KPSBU) Lembang West Java. Primary data obtained discuss with interviewees and join activities of hoof trimming and treatment such as preparing equipment, handling dairy cows, and hoof trimming implementation. Thus secondary data supported by study literature. Hoof trimming in dairy cows at KPSBU Lembang is carried out every 4-6 months. First, farmer should report hoof trimming implantation to officer of health. Officer prepared hoof trimming equipments. Dairy cows were handled before hoof trimming began. Hoof trimming done in a standing position cows starting from the axial and abaxial wall then continued at the sole. Hoof trimming implementation for avoiding hoof infection which disserves dairy cow production.